Human motion detection framework - Suzaimah, Ramli; Kamarul Hawari, Ghazali; Muhammad Faiz, Mohd Ali; Zakaria Hifzan, Hisahuddin (IEEE, 2011)
Ordinary CCTV can only be used to record incidents if it occur. It works without preventing it and it is only useful to be an evidence for the investigation. The purpose of developing this project is as the earlier prevention to avoid crime by giving alert or feedback from the object that was detected from captured video. The captured video in this project will be convert into frame of images and being analyze by using MATLAB software that already consist all the techniques of image processing. The output of this project will be classified if there is any motion or not by using the value of total sum of pixel value from each image data. The classification is actually based on the threshold value. This project indirectly reduce weakness and careless of human guard observation as it give continuous 24-hour monitoring of surveillance video to alert security officers to an intruder potential.